1999
DOI: 10.1128/jvi.73.8.6506-6516.1999
|View full text |Cite
|
Sign up to set email alerts
|

Antiapoptotic and Oncogenic Potentials of Hepatitis C Virus Are Linked to Interferon Resistance by Viral Repression of the PKR Protein Kinase

Abstract: Hepatitis C virus (HCV) is prevalent worldwide and has become a major cause of liver dysfunction and hepatocellular carcinoma. The high prevalence of HCV reflects the persistent nature of infection and the large frequency of cases that resist the current interferon (IFN)-based anti-HCV therapeutic regimens. HCV resistance to IFN has been attributed, in part, to the function of the viral nonstructural 5A (NS5A) protein. NS5A from IFN-resistant strains of HCV can repress the PKR protein kinase, a mediator of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
84
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 241 publications
(88 citation statements)
references
References 86 publications
(124 reference statements)
3
84
1
Order By: Relevance
“…These residues have been described as quite heterogeneous among different HCV-1b isolates. 16,20,39,49,50 On the other hand, serine residues, that are probably implicated in the hyperphosphorylation of NS5A 61,62 were highly conserved in the majority of viral isolates analyzed in this study.…”
Section: Development Of Hcc Is a Well Recognized Complication Of Livementioning
confidence: 74%
See 2 more Smart Citations
“…These residues have been described as quite heterogeneous among different HCV-1b isolates. 16,20,39,49,50 On the other hand, serine residues, that are probably implicated in the hyperphosphorylation of NS5A 61,62 were highly conserved in the majority of viral isolates analyzed in this study.…”
Section: Development Of Hcc Is a Well Recognized Complication Of Livementioning
confidence: 74%
“…[60][61][62]69 It has been reported that HCV-NS5A protein may repress cellular PKR function by a direct interaction via the PKR-bd, which can be abrogated by the presence of mutations within the ISDR. 20 Nevertheless, HCV-interference of the antiviral activity of interferon by mechanisms unrelated to PKR-bd function is also possible, as recently observed. 67,70 Regulation of PKR probably implicates various cellular pathways that may be different depending on the cell type and stimulatory events.…”
Section: Development Of Hcc Is a Well Recognized Complication Of Livementioning
confidence: 87%
See 1 more Smart Citation
“…Intriguingly, PKR is not activated in ZEBOV-infected cells, and VP35 has been shown to actively block PKR activation [160,161]. It has been reported for various viruses that they inhibit PKR-mediated eIF2α phosphorylation to prevent host cell apoptosis [162][163][164]. However, it is not known if the inhibition of PKR in EBOV-infected cells blocks the induction of apoptosis.…”
Section: Interaction Of Filoviruses With Cellular Pathwaysmentioning
confidence: 99%
“…On the other hand, viruses also encode various genes that can antagonize the pro-apoptotic signaling. For example, NS5A protein of HCV is well known for its anti-apoptotic activity although the exact mechanism is still controversial [35,36]; EBV (Epstein-Barr virus)-encoded poly(A) RNAs (EBERs) exhibit striking resistance of IFN-α induced apoptosis in Burkitt's lymphoma cell lines [37].…”
Section: Discussionmentioning
confidence: 99%